Существует ли текстовая картина мира? - Kajtoch, Wojciech (Przegląd Wschodnioeuropejski, 2023)
The article presents the most important opinions in Poland on the interdependence of the linguistic worldview and the text worldview. It tries to answer the title question on the basis of empirical examples. Establishing a text worldview is also a kind of discourse research. The paper proposes to refer to the lexicographic tradition (creating thematic dictionaries) and to the quantitative lexical analysis of the content. The empirical material used in the study consists of three text corpora of 250,000 words each. They contain texts taken from youth magazines from the 1990s. The views presented in the article oppose the findings of the Lublin school of ethnolinguistics.